Characterization of unique metabolites in γ‐aminobutyric acid‐rich cheese by metabolome analysis using liquid chromatography‐mass spectrometry. Issue 11 (5th September 2019) - Hagi, Tatsuro; Nakagawa, Hiroyuki; Ohmori, Hideyuki; Sasaki, Keisuke; Kobayashi, Miho; Narita, Takumi; Nomura, Masaru
Abstract: Fermented dairy products comprise many functional components. Our previous study using fermented milk showed that the γ‐aminobutyric acid (GABA)‐producing Lactococcus lactis 01‐7 strain can produce unique metabolites such as antihypertensive peptides, whereas this study was designed to find the unique metabolites in GABA‐rich cheese using the 01‐7 strain. Metabolites between cheese ripening with the non‐GABA‐producing L . lactis 01‐1 strain (control) and GABA‐rich cheese ripening with a mixture of 01‐1 and 01‐7 strains were compared. GABA and ornithine were detected in GABA‐rich cheese using an amino acid analyzer and citrate was detected in the control cheese using HPLC. Metabolome analysis using LC‐MS showed that peptides with unknown function and those with antihypertensive activity were higher in the GABA‐rich cheese than in the control cheese. Further analysis of the amount of the YLGY derivatives showed that the amount of YL in the GABA‐rich cheese was lower than that in the control. Practical applications: Clarification of metabolites in cheese contributes to the improvement of cheese ripening, thereby providing consumers with unique cheese with good nutritional and functional characteristics. The use of the 01‐7 strain as a cheese starter might provide a functional cheese with antihypertensive‐, antioxidative‐, and anxiolytic‐like activities.